PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI E-COMMERCE DITINJAU DARI UNDANG-UNDANG PERLINDUNGAN KONSUMEN PADA ERA SOCIETY 5.0 (Studi Kasus Toko Online Serba7ribu) - Basri, Herlina; Prayitno, Isnu Harjo; Tajuddin (Rechtsregel : Jurnal Ilmu Hukum, 2025)
This research aims to understand how legal protection is for consumers in e-commerce transactions if a dispute occurs, whether consumer protection regulations accommodate problems that occur in the era of society 5.0 and how the effectiveness of existing dispute resolution can resolve these problems and fulfill a sense of justice. Technological developments are changing the order of human values and life, one of which is the development of the economy in the digital era. The need for laws that can guarantee the rights of parties in business in the current digital era, especially consumer protection, is increasing rapidly as problems become increasingly complex. However, the regulations governing consumer protection were regulations that were born long before digitalization. The research method used is empirical juridical with analytical descriptive research specifications. Data collection was carried out through field studies with observations and interviews with related agencies BPKN, BPSK, LPK-RI, consumers and business actors, and literature studies, data analysis was carried out qualitatively through deductive logical thinking. The Consumer Protection Law, as a regulation that specifically regulates consumer protection, was published in 1999 before digitalization, so it does not regulate consumer problems in digital transactions. Although consumers can use the Information and Electronic Transactions Law as a legal basis, the ITE Law does not yet provide technical regulations regarding consumer protection. Despite regulatory limitations, there are new innovations related to dispute resolution models, namely ODR (Online Dispute Resolution) which is a synergy between ADR (Alternative Dispute Resolution) and ICT (Information and Computer Technology) which is able to simplify the dispute resolution process so that it is not obstructed by space and time by cheap and fast. The author hopes that this paper will achieve results by publishing it in the accredited journal Andalas Nagari Law Review University and can put it in the form of a book with an ISBN.